Effectiveness of primary school principals in managing the implementation of civic and ethical education curriculum - Mulugeta Yayeh Worku (Bahir Dar Journal of Education)
This study was conducted to assess the effectiveness of principals in managing the implementation process of civic and ethical education curriculum. To accomplish this task, a mixed research approach, using both quantitative and qualitative data gathering and analysis methods, was employed. Data sources of the study were 300 Grade Eight students and 25 civic and ethical education teachers, from 15 primary schools found in two woredas (districts) of East Gojjam Administrative Zone, Ethiopia. Data collected through questionnaire and interviews were analyzed both quantitatively and qualitatively. Accordingly, it was explored that the curriculum of civic and ethical education in primary schools studied has been in the process of ‘implementation’ without sufficient and meaningful support and active involvement of principals. Put differently, primary school principals were not found satisfactorily discharging many of their responsibilities in relation to the implementation process of civic and ethical education curriculum. In view of this, areas of intervention that could possibly mitigate the problem are forwarded.